Remote Sensing by Satellite Gravimetry - Gruber, Thomas; Eicker, Annette; Flechtner, Frank; Gruber, Thomas; Eicker, Annette; Flechtner, Frank (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Over the last two decades, satellite gravimetry has become a new remote sensing technique that provides a detailed global picture of the physical structure of the Earth. With the CHAMP, GRACE, GOCE and GRACE Follow-On missions, mass distribution and mass transport in the Earth system can be systematically observed and monitored from space. A wide range of Earth science disciplines benefit from these data, enabling improvements in applied models, providing new insights into Earth system processes (e.g., monitoring the global water cycle, ice sheet and glacier melting or sea-level rise) or establishing new operational services. Long time series of mass transport data are needed to disentangle anthropogenic and natural sources of climate change impacts on the Earth system. In order to secure sustained observations on a long-term basis, space agencies and the Earth science community are currently planning future satellite gravimetry mission concepts to enable higher accuracy and better spatial and temporal resolution. This Special Issue provides examples of recent improvements in gravity observation techniques and data processing and analysis, applications in the fields of hydrology, glaciology and solid Earth based on satellite gravimetry data, as well as concepts of future satellite constellations for monitoring mass transport in the Earth system.
English
Keywords: Research & information: general; terrestrial water storage (TWS); GRACE; GLDAS; TRMM; drought; ENSO; NAO; Turkey; Mass balance; Ice Sheets; Sea-level Rise; Antarctica; CryoSat-2; GRACE-Follow On; GRACE-FO; downward continuation; spectral methods; gravity field recovery; GRACE Follow-On; orbit configuration; synergistic observation; mass transport in the Earth system; GRACE and GRACE follow-on mission; current and future observation concepts and instruments; GRACE TWSA; groundwater level anomaly; downscaling; machine learning; boosted regression trees; glacial sediment; ice mass; satellite gravimetry; Patagonia; ice mass change; SLR; swarm; normal equation combination; coseismic gravity gradient changes; gravity field model; GOCE; Earth$1 (Bs gravity fields; kinematic orbit; kinematic baseline; time-variable gravity; geocenter; reference frames; self-attraction and loading; Level-2 processing; time-variable gravity field; mass change monitoring; next-generation gravity mission; temporal gravity field; numerical closed-loop simulation; satellite mission constellations; mass transport; gravity field satellite missions; GOCE High-Level Processing Facility (HPF), earth gravity field; geoid; spectral enhancement method (SEM), GPS/leveling